Development of Four Unit Processes for Biobased PLA Manufacturing. (15th March 2012) - Hong, Chae Hwan; Kim, Si Hwan; Seo, Ji-Yeon; Han, Do Suck
Abstract : Polylactide (PLA), which is one of the most important biocompatible polyesters that are derived from annually renewable biomass such as corn and sugar beets, has attracted much attention for automotive parts application. The manufacturing method of PLA is the ring-opening polymerization of the dimeric cyclic ester of lactic acid, lactide. For the stereocomplex PLA, we developed the four unit processes, fermentation, separation, lactide conversion, and polymerization. Fermentation of sugars to D-lactic acid is little studied, and its microbial productivity is not well known. Therefore, we investigated D-lactic acid fermentation with a view to obtaining the strains capable of producing D-lactic acid, and we got a maximum lactic acid production 60 g/L. Lactide is prepared by a two-step process: first, the lactic acid is converted into oligo(lactic acid) by a polycondensation reaction; second, the oligo(lactic acid) is thermally depolymerized to form the cyclic lactide via an unzipping mechanism. Through catalyst screening test for polycondensation and depolymerization reactions, we got a new method which shortens the whole reaction time 50% the level of the conventional method. Poly(L-lactide) was obtained from the ring-opening polymerization of L-lactide. We investigated various catalysts and polymerization conditions. Finally, we got the best catalyst system and the scale-up technology.